Improved children`s motor learning of the basketball free shooting pattern by associating subjective error estimation and extrinsic feedback - de Carvalho da Silva, L.; Ferro Pereira-Monfredini, C.; Teixeira, L. A. (Journal of Sports Sciences, 2017)
This study aimed at assessing the interaction between subjective error estimation and frequency of extrinsic feedback in the learning of the basketball free shooting pattern by children. 10- to 12-year olds were assigned to 1 of 4 groups combining subjective error estimation and relative frequency of extrinsic feedback (33% × 100%). Analysis of performance was based on quality of movement pattern. Analysis showed superior learning of the group combining error estimation and 100% feedback frequency, both groups receiving feedback on 33% of trials achieved intermediate results, and the group combining no requirement of error estimation and 100% feedback frequency had the poorest learning. Our results show the benefit of subjective error estimation in association with high frequency of extrinsic feedback in children`s motor learning of a sport motor pattern.